The Vertical-Tube Solar Collector: A Low-Cost Design Suitable for Temperate High-Latitude Locations - Juanico, Luis Eduardo (2014)
A new low-cost solar collector based on thick (4.5′′) vertical tubes related to the previous design based on long 1.5′′ plastic hoses connected directly between water-grid supply and consumption is presented. This novel design could noticeably improve its performance for temperate locations mid and high latitudes, as was demonstrated by dynamic thermal modeling. This tool has been useful for understanding the particular characteristics of this kind of water-pond collector and besides, for noticeably improving its performance by optimizing its parameters, like tube diameter and number of glazing layers. By this way, the optimized design could fully satisfy the household demand up to midnight along the whole year for Buenos Aires (35°S) and during summers (remaining as a useful preheater for the whole year) for Ushuaia (55°S). Besides, its high simplicity makes it available for user’s own construction, costing down 50 dollars for a single-family unit.